2023
DOI: 10.18632/aging.204895
|View full text |Cite
|
Sign up to set email alerts
|

A novel LncRNA SPIRE1/miR-181a-5p/PRLR axis in mandibular bone marrow–derived mesenchymal stem cells regulates the Th17/Treg immune balance through the JAK/STAT3 pathway in periodontitis

Abstract: Periodontitis is a microbial-related chronic inflammatory disease associated with imbalanced differentiation of Th17 cells and Treg cells. Bone marrow-derived mesenchymal stem cells (BM-MSCs) possess wide immunoregulatory properties. Long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) contribute to the immunomodulation in the pathological mechanisms of inflammatory diseases. However, critical lncRNAs/miRNAs involved in immunomodulation of mandibular BM-MSCs largely remain to be identified. Here, we explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…They play important regulatory roles in the differentiation of MSCs into adipocytes; however, few studies have explored the role of lncRNAs in adipogenic differentiation. 16 Our previous research study based on transcriptome sequencing confirmed that various lncRNAs regulate adipogenic differentiation in BMSCs. However, the regulation of adipogenic differentiation by lncRNA in BMSCs remains largely unexplored.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…They play important regulatory roles in the differentiation of MSCs into adipocytes; however, few studies have explored the role of lncRNAs in adipogenic differentiation. 16 Our previous research study based on transcriptome sequencing confirmed that various lncRNAs regulate adipogenic differentiation in BMSCs. However, the regulation of adipogenic differentiation by lncRNA in BMSCs remains largely unexplored.…”
Section: Introductionmentioning
confidence: 83%
“…Among these, long-chain noncoding RNAs (lncRNAs) have received increasing attention due to their important regulatory roles. , LncRNAs are the most abundant type of noncoding RNA and comprise >200 nt long transcripts that play important roles in cell differentiation, growth, development, and onset of many diseases. , LncRNAs exhibit multiple regulatory functions and participate in several important biological processes. They play important regulatory roles in the differentiation of MSCs into adipocytes; however, few studies have explored the role of lncRNAs in adipogenic differentiation . Our previous research study based on transcriptome sequencing confirmed that various lncRNAs regulate adipogenic differentiation in BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst many of these RNAs may be circulating from a variety of sources and may also be present within non-cancer populations, combinations of these molecules specifically linked with bone remodeling may provide a potential means of monitoring pre-metastatic niche development. For example, SPIRE1 was found to be one of the most abundant of the RNAs analyzed and has known roles in immunomodulation of bone marrow mesenchymal stem cells ( Shao et al, 2023 ). Further research into this area may provide the potential to identify patients at risk of bone metastasis at the earliest stages.…”
Section: Discussionmentioning
confidence: 99%
“…With their capacity for self-renewal and potent osteogenic differentiation capacities, bone marrow-derived mesenchymal stem cells (BMSCs) are regarded as an essential stem cell source for bone regeneration. , The fate determination of BMSCs was manipulated by a wide range of factors, especially immune factors. Accumulating evidence has indicated that various immune cells interact with BMSCs in the bone defect area and bone marrow cavity. , Recently, much attention has been focused on the crucial function of macrophages in the recruitment and differentiation of MSCs throughout the process of bone regeneration .…”
Section: Introductionmentioning
confidence: 99%